2016
DOI: 10.1007/s10616-016-9972-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 15-lipoxygenase-1 in the regulation of breast cancer cell death induced by sodium butyrate

Abstract: 15-Lipoxygenase-1 (15-Lox-1) as a member of fatty acid dioxygenases family has received considerable attention as an effector of cancer cell growth. The relevance of sodium butyrate on 15-Lox-1 pathway has not been determined in breast cancer. This study is aimed to investigate the possible involvement of 15-Lox-1 in the regulation of breast cancer cell growth by sodium butyrate. MTT assay was used to assess the cytotoxicity effect and Annexin-V-FITC staining was applied for detection of apoptosis using flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…To address this, we set up a connected set of experiments to characterize the possible anticancer effect of sodium butyrate on breast cancer cell growth as well as normal breast cells. The results of the current study also our previous study [ 20 ] have revealed that sodium butyrate deceased the rate of viable breast cancer cells in a dose and time dependent manner. In our previous study the involvement of 15-lipoxygenase in the regulation of breast cancer cell growth induced by sodium butyrate was explored [ 20 ], however in the present study the exact mechanism underlying sodium butyrate-induced cell death in human breast cancer is perused.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To address this, we set up a connected set of experiments to characterize the possible anticancer effect of sodium butyrate on breast cancer cell growth as well as normal breast cells. The results of the current study also our previous study [ 20 ] have revealed that sodium butyrate deceased the rate of viable breast cancer cells in a dose and time dependent manner. In our previous study the involvement of 15-lipoxygenase in the regulation of breast cancer cell growth induced by sodium butyrate was explored [ 20 ], however in the present study the exact mechanism underlying sodium butyrate-induced cell death in human breast cancer is perused.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the current study also our previous study [ 20 ] have revealed that sodium butyrate deceased the rate of viable breast cancer cells in a dose and time dependent manner. In our previous study the involvement of 15-lipoxygenase in the regulation of breast cancer cell growth induced by sodium butyrate was explored [ 20 ], however in the present study the exact mechanism underlying sodium butyrate-induced cell death in human breast cancer is perused. In support of this, the appropriate range of sodium butyrate concentrations (0.1–20 mM) at different time intervals were investigated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although NaB was found be beneficial to several diseases (He et al 2016, Li et al 2016, Salimi et al 2016, Subramanian et al 2016, little is known about its protection against DN. To the best of our knowledge, there has been only one study that reported NaB protection against DN (Khan & Jena 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The protection conferred by HDAC inhibition may be associated with the upregulation of histone acetylation at the promoter region of nfe2l2. NaB, a natural short-chain fatty acid, is an HDAC inhibitor that affects proliferation, differentiation, and apoptosis of cell (83). Dong et al demonstrated that NaB may activate Nfe2l2 at the transcriptional level to ameliorate DN possibly by inhibiting HDAC activity (60).…”
Section: Epigenetic Modifications Of Nrf2 By Pharmacological Agentsmentioning
confidence: 99%